Treatment of the nevus of Ota with the 1064-nm Q-switched Nd:YAG laser - Akpınar Kara, Yeşim (The European Research Journal, 2019)
Nevus of Ota is a benign hamartoma which presenting as blue-gray hyperpigmented patches on the face and mucous membranes usually within the distribution of first and second branches of the trigeminal nerve. It may occur at birth or during adolescence and the nevus of Ota is very common seen in Japan and east countries. The pigmentation varies and can be dark brown to blue to black-blue. We report a 31-year-old female patient with the nevus of Ota. The Q-switched Nd:YAG laser, had a spot size of 3 mm, an 8 Hz repetition rate, 720 mj/cm2 fluence. The patient's lesion improved in a rate of 60% with a single session. The Q-switched Nd:YAG laser has a significant effect in treating the nevus of Ota.